Peran Kepuasan Kerja dalam Memediasi Pengaruh Karakteristik Perusahaan dan Budaya Organisasi terhadap Loyalitas Karyawan pada Bank Aceh Syariah Kantor Cabang Utama Banda Aceh - Muhammad Ranaldi; Lukman Ibrahim; Kurnia Asni (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi, 2026)
This study aims to analyze the influence of company characteristics and organizational culture on employee loyalty, with job satisfaction serving as a mediating variable at Bank Aceh Syariah Main Branch Office, Banda Aceh. The research employed a quantitative approach using an explanatory research design. The study population consisted of all employees, with a sample of 166 respondents selected through proportionate stratified random sampling. Data were collected using a structured questionnaire based on a five-point Likert scale and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach. The findings reveal that company characteristics and organizational culture have a positive and significant effect on job satisfaction. However, neither company characteristics nor organizational culture has a significant direct effect on employee loyalty. In contrast, job satisfaction has a positive and significant effect on employee loyalty and serves as a strong mediating variable in the relationship between the independent variables and employee loyalty. These results indicate that employee loyalty is influenced more by internal psychological factors, particularly job satisfaction, than by the organization's structural characteristics directly. The study highlights the importance of enhancing job satisfaction as a primary strategy for strengthening employee loyalty. Organizations should not only improve their organizational systems and workplace culture but also ensure that implemented policies create positive work experiences for employees. This research provides an empirical contribution to the development of human resource management literature, particularly within the Islamic banking sector.